Unseen Cinema - Light Rhythms: Music and Abstraction Early American Avant-Garde Film 1894-1941 - Beheim, Eric; Antheil, George; Sosin, Donald (Unseen Cinema, 2005)
The rhythmic elements of cinema are explored by artists and filmmakers fascinated by the abstract qualities of light. The American authors of avant-garde classics "Le Retour á la raison" (1923), "Ballet mécanique" (1923-1924), "Anémic cinéma" (1926), and "Une Nuit sur le Mont Chauve" (1934), are finally acknowledged for their seminal artistic achievements made in Europe. Pioneer abstract films by Ralph Steiner, Mary Ellen Bute, Douglass Crockwell, Dwinnell Grant, and George Morris are compared and contrasted with Hollywood montages created by Ernst Lubitsch, Slavko Vorkapich, and Busby Berkeley. For the first time on video, composer George Antheil's original 1924 score accompanies Fernand Léger and Dudley Murphy's film "Ballet mécanique", a truly avant-garde cacophony of image and sound. [Cover]